Influência da irrigação e do manejo da desfolha sobre o balanço hídrico e produção de forragem de Tifton 85 - Rodrigues, Geraldo José (2017)
The studies with the use of irrigation systems in pastures focus on assessing productive responses of forage plants. However, it is important to evaluate the use of technologies and favor the application of the knowledge generated in this productive environment considering the relationships between soil-water-plant-atmosphere and the management adopted for the pastoral environment. During the summer, there is high atmospheric evaporative demand for the subtropical region of southern Braziland and although the distribution of rainfall are relatively uniform it is common to see water scarcity for agricultural crops due to possible periods of insufficient precipitation to meet the evaporative demand atmosphere. In order for this problem to be circumvented, it is fundamental to conduct studies with a focus on the use of irrigation and soil water balance over pastoral environments. This study evaluated the use of irrigation and management of peeling forage Tifton 85 and their influence on soil water balance and the dry weight and total output; to determine the baseline culture coefficients for Tifton 85 through the calibration and validation of the SIMDualKc model. In the agricultural year 2015/16 an experiment was carried out on Tifton 85 pasture established four years ago. The experimental design was completely randomized with treatments distributed in factorial arrangement, with two qualitative levels of water management (irrigated and non irrigated) and four quantitative levels of defoliation frequency (124, 248, 372 and 744 degrees day (GD, ° C) of thermal accumulation). 12 mm irrigations were applied by conventional spray when soil moisture was less than 85% of the field capacity. The management of defoliation (cuts) was performed mechanically at a height of 0.15 m. This management was carried out for the spring, summer and autumn periods. Soil moisture was monitored continuously for the 0.00 - 0.50 m layer using FDR sensors and the readings were stored in a datalogger. Daily reference evapotranspiration was determined by the method of Penman Monteith from the meteorological data observed in an automatic station installed 300 m from the experimental area. The following productive variables were evaluated: canopy height, leaf: stem ratio, canopy height variation, dry leaf mass, dry mass of dead material, daily dry mass accumulation rate and dry mass production showed interaction between defoliation and evaluation period. Differences were observed between the forage mass and the dry mass of stalk for frequency of defoliation and the results presented a quadratic behavior. The calibration and validation of the SIMDualKc model was efficient and allowed to partition the daily evapotranspiration of the crop and to estimate the basal crop coefficients for the Tifton 85 forage.